Imaging response assessment for CNS germ cell tumours: consensus recommendations from the European Society for Paediatric Oncology Brain Tumour Group and North American Children's Oncology Group. Issue 5 (May 2022) - Morana, Giovanni; Shaw, Dennis; MacDonald, Shannon M; Alapetite, Claire; Ajithkumar, Thankamma; Bhatia, Aashim; Brisse, Hervé; Jaimes, Camilo; Czech, Thomas; Dhall, Girish; Fangusaro, Jason; Faure-Conter, Cecile; et al.
Summary: Homogeneous and common objective disease assessments and standardised response criteria are important for better international clinical trials for CNS germ cell tumours. Currently, European protocols differ from those of North America (the USA and Canada) in terms of criteria to assess radiological disease response. An international working group of the European Society for Paediatric Oncology Brain Tumour Group and North American Children's Oncology Group was therefore established to review existing literature and current practices, identify major challenges regarding imaging assessment, and develop consensus recommendations for imaging response assessment for patients with CNS germ cell tumours. New clinical imaging standards were defined for the most common sites of CNS germ cell tumour and for the definition of locoregional extension. These new standards will allow the evaluation of response to therapy in patients with CNS germ cell tumours to be more consistent, and facilitate direct comparison of treatment outcomes across international studies.